Nerve Growth Factor Suppresses Prostate Tumor Growth - Mitsuhiro Goda; Saori Atagi; Keisuke Amitani; Narumi Hobara; Yoshihisa Kitamura; Hiromu Kawasaki (Elsevier, 2010)
Nerve growth factor (NGF) facilitates reinnervation of perivascular nerves that regulate vascular tone and blood flow. This study investigated whether NGF prevents tumor growth by promoting neuronal regulation of tumor blood flow. The growth rate of DU145 prostate carcinoma cells subcutaneously implanted into nude mice was significantly inhibited by subcutaneous NGF administration. Significant suppression of tumor growth continued after withdrawing NGF. NGF increased vascular smooth muscle cells in tumor tissues, but had no cytotoxic action on tumor cells in vitro. These results suggest that NGF prevents tumor growth via an indirect effect, probably innervation or maturation of the tumor neovasculature. Keywords:: nerve growth factor, prostate tumor growth, angiogenesis